Computer Support for Cooperative Design - Bødker, Susanne; Ehn, Pelle; Knudsen, Jørgen Lindskov; Kyng, Morten; Madsen, Kim Halskov (DAIMI Report Series, 1988)
Computer support for design as cooperative work is the subject of our discussion in the context of our research program on Computer Support in Cooperative Design and Communication. We outline our theoretical perspective on design as cooperative work, and we exemplify our approach with reflections from a project on computer support for envisionment in design --- the APLEX and its use. We see envisionment facilities as support for both experiments with and communication about the future use situation. As a background we sketch the historical roots of our program --- the Scandinavian collective resource approach to design and use of computer artifacts, and make some critical reflections on the rationality of computer support for cooperative work.